Children's experiences of the journey between home and school: A qualitative synthesis using meta-ethnography. (July 2022) - Morris, Stephanie; Lawlor, Emma R.; Foley, Louise; Summerbell, Carolyn; Panter, Jenna; Adams, Jean; Jago, Russell; Pollard, Tessa M.
Abstract: This paper uses meta-ethnography to synthesise qualitative and ethnographic studies of children's (aged 5–13) experiences of socio-material environments on their school journey. Most of the 21 papers (18 studies) identified from the systematic search were from high-income countries and used self-report qualitative methods. Our synthesis shows children can feel vulnerable, but also negotiate journeys and manage risks, enjoy shared and solitary mobility, and explore their material environments. School journeys offer children a place to learn and develop agency within their socio-material environments. Attending to these wider benefits of school journeys, alongside supporting children to develop active modes attuned to the risks associated with these journeys, could improve the reach and impact of active school travel initiatives. Highlights: Children often feel vulnerable on their journey to school. Children travelling actively negotiate and manage risk. The journey to school can be a sociable and exploratory learning experience. Active school travel interventions should attend to the experiences of children.